Investigação de complexos binucleares de K+ E CU(II) com ligantes 1,3-diariltriazenidos simétricos - Silva, Aline Marques da (2006)
At work present it synthesized and determined itself the molecular structure of a copper complex (II) and another of potassium in which both involve triazenides ligands monocatenados previously deprotonated. The reaction between hydroxide of solid potassium and it pre-ligand 1,3-bis(4-nitrophenyl)triazene, in methanol, originated the triazenide complex [K(O2NC6H4NNNC6H4NO2)]2 (1), which crystallizes in the crystalline triclinic system, space group P(-1), with cell parameters a = 7,4932(6) Å, b = 9,5195(6) Å and c = 9,9156(6) Å, α = 83,631(5)º, β = 79,577(3)º and γ = 82,453(5)º, V = 686,84(8) Å3, Z = 2. The refinement of the crystalline and molecular structure converged to the disagreement indices R1 = 0,0433 and wR2 = 0,1303. The crystalline of (1) it reveals the identity of a binuclear complex of K+ three-coordinated in a first instance. The molecular unit dímeras involve a supramolecular auto-association through K O secondary interactions which results in a supramolecular three-dimensional 3-D arrangement. The reaction between copper acetate (II) and it pre-ligand 1,3-bis(2-fluorophenyl)triazene previously deprotonated with sodium hydroxide in pyridine/methanol in the proportion of 1:2, originated the triazenide complex [Cu2(FC6H4NNNC6H4F)4] (2) which crystallizes in the crystalline system monoclinic, space group P21/c, with cell parameters a = 22,760(5) Å, b = 11,095(5) Å, c = 18,691(5) Å, β = 101,8440(5)º, V = 4619(3) Å3, Z = 4. The refinement of the crystalline and molecular structure converged to the disagreement indices R1 = 0,0770 e wR2 = 0,1769. The crystalline structure of (2) it is formed by a binuclear complex neutral of copper (II), with the metallic ions individually tetracoordenados. The molecule of the complex (2) it introduces two rings of eight members who suffer an intersection to each other through the copper(1) and copper(2) ions, thus each metallic center introduces a geometry of pyramidal coordination of squared base. Both complexes (1) and (2) were characterized by the determination of the melting point and UV/Vis and infrared espectroscopy in the, beside the single crystal X-ray diffraction analysis.